The Law on the Hijab for Muslim Women from the Perspective of Ahkam Interpretation - Arum Setyowati; Ali Junnifar (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2025)
The hijab is a type of clothing used to cover the private parts of Muslim women. The legal hijab is certain or absolute for adult women who believe in wearing it. Allah SWT's command regarding Muslim women wearing the hijab is found in the QS. Al-Ahzab verse 59. This research aims to analyze the texts of the Qur'an regarding the book Al Jami' li Ahkaam Al Qur'an by Shaykh Imam Al Qurthubi from the Malikiyyah group, the book Ahkam Al Qur'an by al-Kiya al-Harasi from the Syafi'iyyah group, and the book Ahkam Al Qur'an by al-Jassas from the Hanafiyah group, which relates to the hijab for Muslim women. The research method used is a literature study carried out by collecting library data, reading and taking notes, as well as managing research materials regarding journal contents related to hijab laws for Muslim women. The style of interpretation uses tafsir ahkam (interpretation of legal verses). In the book Al Jami' li Ahkaam Al Qur'an by Sheikh Imam Al Qurthubi, it is explained that Allah SWT ordered women to wear the hijab according to sharia, starting with the wives of the Prophet and his daughters. The book also explains the commandment for free women to wear the hijab to distinguish them from slave women. Allah SWT also ordered them to stretch their hijab, meaning they should cover their heads and faces so that they are recognized as free women. This is so that they are more easily recognized, so that they are not disturbed, meaning to be recognized as women who maintain their honor, guard themselves, and always try to protect their genitals. The book Ahkam Al Qur'an by al-Kiya al-Harasi explains that the hijab is a cloak, Allah commands Muslim women to cover their faces and heads. However, this is not obligatory for slave women. The book Ahkam Al Qur'an by al-Jassas explains that Allah commands believing women to cover their entire bodies. This would make it more likely that they were free women and would not be harmed. Slave women were not ordered to cover their heads and faces. After reviewing three books used as references: